“Tombstone” anterior st‐segment elevations secondary to acute pericarditis: the role of two‐dimensional echocardiogram - Jain, Avanindra (Clin Cardiol, 2009)
Prompt and appropriate administration of thrombolytic therapy is important for patients with acute myocardial infarction. However, in addition to contraindications, alternative causes of ST‐segment elevation should be considered before thrombolytic therapy is instituted. A patient with marked ST‐segment elevation in the anterior leads suggestive of acute ischemia is presented. Because of lack of ischemic symptoms, an echocardiogram was performed. This showed mild generalized hypokinesis, and thrombolytic therapy was not administered. Subsequent ECGs demonstrated evolutionary findings consistent with pericarditis. In selected patients a two‐dimensional echocardiogram, which can be easily performed at patient bedside, will help in appropriate patient management.